PENGARUH KESULITAN LITERASI NUMERASI BERDASARKAN KEMAMPUAN BERPIKIR KRITIS DAN SELF-EFFICACY MATEMATIKA SISWA SEKOLAH DASAR - Nisrina Nurul Aini; Danuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the difficulties of learning numeracy literacy of grade V students at SD Negeri 1 Pecekelan Wonosobo by reviewing the ability to think critically and self-efficacy in mathematics. Numeracy literacy is an essential competency in elementary school mathematics learning, but the achievements of Indonesian students are still below international standards. The difficulty of numeracy literacy is not only related to the understanding of mathematical concepts, but is also influenced by the ability to think critically as a cognitive aspect and self-efficacy as an affective aspect. This research uses a qualitative approach with a case study type. The subject of the study is class V students in the context of inclusion classes. Data collection techniques are carried out through observation, interviews, and documentation, with inductive data analysis through the process of reduction, presentation, and drawing conclusions. The results of the study show that the difficulties in students' numeracy literacy are seen in the ability to understand contextual problems, interpret data, and draw logical conclusions. Low critical thinking skills affect students' inability to formulate systematic problem-solving strategies. In addition, low mathematical self-efficacy is shown through a lack of confidence, doubt in answering questions, and a tendency to avoid tasks that are considered difficult. These findings confirm that numeracy literacy difficulties are a multidimensional phenomenon influenced by the interaction between cognitive and affective factors. This research contributes to providing a more comprehensive understanding of the dynamics of numeracy literacy learning difficulties in the context of inclusive elementary schools and offers a conceptual basis for the development of adaptive learning strategies to improve students' critical thinking skills and mathematical self-efficacy.